Efektivitas Senam Otak sebagai Upaya Preventif Pengendalian Demensia pada Lansia di Posyandu Lansia Handayani 2 Dukuhwaluh - Anesa Prasasti Abdillah; Indri Heri Susanti; Pramesti Dewi (Universitas Muhammadiyah Manado, 2025)
Dementia is a progressive syndrome of cognitive decline frequently experienced by older adults, characterized by impairments in memory, behavior, and daily living activities. Its prevalence continues to rise globally and regionally, including in Southeast Asia. Non-pharmacological efforts such as brain gym are considered beneficial to maintain brain activity, stimulate motor coordination, and reduce the risk of cognitive impairment. This community service program was implemented to address the low level of knowledge about dementia and brain gym among older adults at Posyandu Lansia Handayani 2 Dukuhwaluh, Banyumas. The intervention was conducted in three sessions involving 21 elderly participants. In the first session, cognitive function was assessed using the Mini Mental State Examination (MMSE) and a pre-test of knowledge, followed by dementia education, brain gym demonstration, and distribution of monitoring sheets for family use at home. The second and third sessions repeated MMSE and post-test assessments, performed additional brain gym demonstrations, and, in the final session, measured participants’ interest in the activity. Results showed a gradual increase in MMSE scores from an average of 26 to 28 and finally 30, indicating all participants reached the normal category. Knowledge levels improved markedly from predominantly low to predominantly high (mean score 93). Participants’ skills in demonstrating five brain gym movements also improved over time, although some movements were initially perceived as difficult. At the end of the program, 57% of older adults expressed high interest and 43% moderate interest in continuing brain gym independently. These findings confirm that dementia education combined with brain gym demonstration is effective in improving cognitive function, knowledge, skills, and interest among older adults and can serve as a preventive strategy for dementia control at the community level.